"It inspires me and suddenly the ideas come": exploring the use of cultural venues in mental health care. Issue 1 (2nd January 2022) - D'Andrea, Federica; Tischler, Victoria
ABSTRACT: Aims: This study aimed to explore the experiences of a group of adults with a history of substance misuse taking part in a novel, multi-centre cultural intervention: Creative Conversations, including the impact of the project on participants' mental health. Methods: A qualitative approach was used including a Visual Matrix and observation in order to explore the experiences of 10 participants recruited from drug and alcohol services. Results: The results indicated positive impacts on mental health including a growing sense of competence, engagement, social integration and a sense that the project provided therapeutic support that translated into integrating creative activities into their everyday habits. Conclusions: Cultural interventions like Creative Conversations demonstrate positive impacts on mental health, engaging individuals who may find it difficult to access services such as those with substance misuse issues, and play an important role in sustaining and promoting mental wellbeing in the community. Despite positive findings, projects such as this require adequate staff training and sustained funding in order to provide wider benefits to those with mental health problems.